Rsv Infection in Infants Admitted to Paediatric Intensive Care Unit - López Escobar, Alejandro; Fernández Díaz, M.; Jimeno Ruiz, Sara; Llana Martín, I.; Benedit Gómez, M. (My University, 2024)
Objectives: Description of RSV infection in infantes below two months old admitted to Paediatric Intensive Care Unit (PICU). Methods: Descriptive and retrospective study of infants less than two months old admitted to PICU with the diagnosis of RSV infection from january-2004 to December-2010. Results: 53 children below two months of age were admitted to PICU hospital during the period of study with diagnosis of RSV infection. 25 from the emergency department and 28 from the paediatric floor. The causes of admission were apnoea (in 21,4%of the cases) and respiratory distress (in 78,6% of the cases). 30,1 % of these children were preterm. 94,3 % of the infants admitted developed bronchiolitis, 17 % presented apnoea. 76,9% were treated with epinefrine and 32,7% with albuterol. 26,4% required antibiotics. Ventilatory assistance was needed in 65% of the patients (CPAP in 50% and ventilatory support in 15%)..They required a mean FiO2 of 30.8+/-16.1% for a period of 3.85+/-3.54d. Mean PCO2 was 57.4+/-14 mmHg. A chest X-ray was performed in 75.5% of the children and showed pneumoniae or atelectasia in 43,2% of the cases. Discussion: Patients with a diagnosis of RSV infection admitted to PICU develope bronchiolitis in a high percentage. Epinefrine was the main treatment used. Mainly 50% of these infants required respiratory assistance.